Demographic transition in South Korea: implications of falling birth rates - Chae Young Kim; Sung-Hoon Chung (The Korean Pediatric Society, 2024)
This review examines the critical issues of declining total fertility rates (TFRs) and aging populations in East Asia with special focus on South Korea. It provides a comprehensive analysis of TFR trends, aging demographics, and the policy responses of these nations to the low-fertility crisis. This study highlights the intricate tapestry of the factors contributing to these demographic shifts, including economic, social, and cultural influences. It also examines the effectiveness of various prenatal policies implemented across these countries, offering insight into their successes and limitations. Furthermore, it explores the role of immigration as a potential solution to the structural challenges posed by low birth rates. This review underscores the importance of multifaceted strategies for addressing the complex demographic challenges faced by South Korea.